(untitled) (Global Journal of Management and Business Research, 2021)
In the fast-changing business environment, workforce diversity is a critical tool for organizations to gain competitive advantage. This research has been conducted to explore the relationship between workforce diversity and employee’s perceived performance in the banking sector of Bangladesh focusing on gender, age, and educational level diversity. The data was gathered through a questionnaire from a sample of 322 employees. One-Sample T-test and Chi-Square tests were conducted for data analysis. The results of the study showed that gender and educational level diversity have a significant positive impact on while age diversity does not affect employee’s perceived performance in the banking sector of Bangladesh. In addition, employees perceive these impacts differently based on their age, gender, and educational level. This research may be used for further research to explore more dimensions of diversity taking team dynamics into account.